2019
DOI: 10.1029/2019jf005114
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of the Near‐Bed Particle‐Borne Stress Profile in Aeolian Transport Systems

Abstract: Self‐regulation of sediment transport by wind is widely assumed to derive from the partitioning of momentum from the fluid flow to the particle cloud. Consequently, the fluid stress on the bed surface is suggested by some to drop below that required to entrain particles, while the cloud is sustained by particle ricochet and splash that derive from the impacts of particles moving ballistically along the bed surface. While these theoretical constructs underpin present‐day numerical models of aeolian saltation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…To better explain this problem, we plot the dimensionless Reynolds stress of sand-laden flow in Figure 10. It can be seen from the figure that the characteristics of the dimensionless Reynolds stress profiles are generally consistent with those of O'Brien and Neuman (2019). The difference is that we also have a focus feature between the constant stress region and the near-wall region.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…To better explain this problem, we plot the dimensionless Reynolds stress of sand-laden flow in Figure 10. It can be seen from the figure that the characteristics of the dimensionless Reynolds stress profiles are generally consistent with those of O'Brien and Neuman (2019). The difference is that we also have a focus feature between the constant stress region and the near-wall region.…”
Section: Discussionsupporting
confidence: 80%
“…We believe that since the rules of dimensionless Reynolds stress with the friction wind speed in the outer wake flow region and near wall region are opposite, there must be an intersection point or intersection zone in the middle. As for whether the focus is formed or closer to the intersection zone of O'Brien and Neuman (2019), it requires more in-depth studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If grain speeds increase, then increased transport means that the zone of grainfall on the slipface would increase as well; thus, the size of the bulge would increase as suggested by others (Nickling et al., 2002; Pelletier et al., 2015). Some studies indicate that grain speeds remain approximately constant (Martin & Kok, 2017; O’Brien & McKenna Neuman, 2019; Pähtz & Tholen, 2021), although other work contradicts this (Rasmussen & Sørensen, 2008). Suppose, instead, increased transport is caused by increased grain numbers (e.g., Namikas, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bridges et al (2005) investigate how the angle of the rock face with respect to surface normal, as well as the height above the surface, affects the abrasion rate. The presence of faster moving particles with increasing distance from the surface is predicted by numerical modeling (e.g., Durán et al, 2011) and observed by O'Brien and McKenna Neuman (2019); however, they are few in number as compared to the entire population of saltating grains. Nevertheless, the cumulative number count of particle impacts upon rock surfaces over time at distances well-above the bed could become quite substantial and result in more abrasion with increasing height due to increasing levels of kinetic energy in the saltation cloud (Anderson, 1986), to a maximum (e.g., Sharp, 1964;Wilshire et al, 1981).…”
Section: Introductionmentioning
confidence: 88%